2000
DOI: 10.1038/35013106
|View full text |Cite
|
Sign up to set email alerts
|

CTCF mediates methylation-sensitive enhancer-blocking activity at the H19/Igf2 locus

Abstract: The Insulin-like growth factor 2 (Igf2) and H19 genes are imprinted, resulting in silencing of the maternal and paternal alleles, respectively. This event is dependent upon an imprinted-control region two kilobases upstream of H19 (refs 1, 2). On the paternal chromosome this element is methylated and required for the silencing of H19 (refs 2-4). On the maternal chromosome the region is unmethylated and required for silencing of the Igf2 gene 90 kilobases upstream. We have proposed that the unmethylated imprint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
1,140
4
10

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,374 publications
(1,196 citation statements)
references
References 28 publications
29
1,140
4
10
Order By: Relevance
“…DMRs are CpG rich and subject to epigenetic modifications. These imprinting control regions are often complex with multiple functions acting to repress genes when methylated, or serving as boundary elements when unmethylated (the boundary element 21,22 indirectly affects expression of neighbouring genes). Some DMRs also function as silencer elements when unmethylated 23 , a function that is apparently abolished when the DMR is methylated.…”
Section: Epigenetic Asymmetry Between Parental Genomesmentioning
confidence: 99%
“…DMRs are CpG rich and subject to epigenetic modifications. These imprinting control regions are often complex with multiple functions acting to repress genes when methylated, or serving as boundary elements when unmethylated (the boundary element 21,22 indirectly affects expression of neighbouring genes). Some DMRs also function as silencer elements when unmethylated 23 , a function that is apparently abolished when the DMR is methylated.…”
Section: Epigenetic Asymmetry Between Parental Genomesmentioning
confidence: 99%
“…This abnormality in Wilms' tumors is inevitably linked to a gain in methylation, localized to the 5 0 sequences and transcribed region of the closely linked and reciprocally imprinted H19 gene (Moulton et al, 1994;Steenman et al, 1994;Taniguchi et al, 1995). Recently, the methylation status of the binding site of insulator protein, CTCF, in the upstream region of H19 has been suggested to be critical in the regulation of the H19/IGF2 locus (Bell and Felsenfeld, 2000;Hark et al, 2000). Allelic expression of H19 and IGF2 is regulated by the binding of CTCF insulators to parent-specific DNA methylation sites in an imprinting control center (ICR) located between the two genes in mouse (Bell and Felsenfeld, 2000;Hark et al, 2000).…”
Section: T Kawakami Et Almentioning
confidence: 99%
“…Recently, the methylation status of the binding site of insulator protein, CTCF, in the upstream region of H19 has been suggested to be critical in the regulation of the H19/IGF2 locus (Bell and Felsenfeld, 2000;Hark et al, 2000). Allelic expression of H19 and IGF2 is regulated by the binding of CTCF insulators to parent-specific DNA methylation sites in an imprinting control center (ICR) located between the two genes in mouse (Bell and Felsenfeld, 2000;Hark et al, 2000). The 5 0 region of human H19 contains seven CTCF-binding sites (Hark et al, 2000), but only the sixth of the seven CTCFbinding sites has been demonstrated to have allelespecific methylation in humans (Takai et al, 2001).…”
Section: T Kawakami Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Various insulators have been found from Drosophila and vertebrates, including chicken, mouse and human. [10][11][12][13] These insulators have two conserved properties, 14 one is an enhancer-blocking activity in which the insulator blocks enhancer/promoter interaction when placed in between them and the other is the protection from the position effect. Specifically, by flanking the promoter/reporter cassette with two insulators, the cassette will be isolated from the local chromosomal environment and therefore be protected from the position effect.…”
Section: Introductionmentioning
confidence: 99%